Analysis of Online Buying and Selling Viewed from an Islamic Economic Perspective (Case Study of the Onlineshop HB Store Medan) - Revita Sari; Muhsin Lambok (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine online buying and selling transactions at the HB Store and to find out the implications of buying and selling at the HB Store after implementing this online system. This research method uses a descriptive qualitative method, a type of field research. With data collection techniques from interviews, observations, documentation. Furthermore, from the results of the study, that buying and selling online is permissible because it has the same context and method as buying and selling greetings. Transactions at the HB Store include ordering, shipping payments. As for the implications of buying and selling at the HB Store, after using the online system, marketing for buying and selling is easier by simply uploading an image. with online marketing these goods will reach various regions. Buying and selling activities can also be carried out at home without taking a long time. Income from online business has slowly increased.